Kajian Potensi Objek Daya Tarik Wisata Alam Karst Rammang-Rammang di Kabupaten Maros Provinsi Sulawesi Selatan - Isramirawaty Agus Mandong; Tati Budiarti; Aris Munandar (Jurnal Lanskap Indonesia, 2023)
The Rammang-Rammang Karst landscape is part of the Maros-Pangkep Karst Area (KKMP) which is the second largest and most beautiful in the world after the karst areain China. This research aimed to examine the potential for existing of the Rammang-Rammang Karst landscape and assess the feasibility of developing the RammangRammang Karst potential. The research location is in the Rammang-Rammang Karst landscape which is located in Salenrang Village, Bontoa District, Maros Regency, South Sulawesi Province. This research was conducted from October 2019 to December 2021. This research used one data analysis, namely an Analysis of Operational Areas – Natural Tourism Objects and Attractions (ADO-ODTWA) to identify potential development of the Rammang-Rammang Karst landscape. The findings are overall, the Rammang-Rammang Karst landscape has a development feasibility index of 81% indicating that it has a high potential to be developed for ecotourism areas. The potential with each of these feasibility indexes consists of 97% tourist attraction, 93% accessibility, 42% accommodation, and 92% facilities and infrastructure. The accommodation criteria have a low eligibility index compared to the others.